The Intersection of Literature and Da'wah: Reflections of The Third-World Muslim Society in V.S. Naipaul's Beyond Belief Islamic Excursions Among The Converted Peoples - Nurholis, Nurholis; Asy Syamil, Muhammad Fikri (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study examines the communities in four countries—Indonesia, Iran, Pakistan, and Malaysia in Beyond Belief: Islamic Excursions Among the Converted Peoples, which portrays Muslim Through the character of